Captain Underpants and the attack of the talking toilets - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Captain Underpants, 1999)
Principal Krupp once again turns into the superhero Captain Underpants in order to save the world, and Jerome Horwitz Elementary School, from the evil talking toilets and the Turbo Toilet 2000.